Nilai Karakter Mandiri Anak Usia Dini Dalam Lirik Lagu Anak-Anak Karya Pak Kasur - Diah Sekar Rini; Nurfuadi Nurfuadi (Departement of Mathematics Education, 2023)
This study examines several children's songs by Pak Kasur regarding aspects of independent character for early childhood. The purpose of this study was to find and describe the value of independent characters contained in the lyrics of children's songs by Pak Kasur, and to find out how to teach singing Pak Kasur's songs as independent character development in early childhood. The method used in this research is a qualitative research method with the type of library research. The researcher examines and analyzes the contents of the lyrics of several children's songs by Pak Kasur as a source of data related to aspects of the independent character of early childhood. The results of this study indicate that the cultivation of independent character values ​​for early childhood can be done through the media of children's songs, in this case the songs by Pak Kasur. The results of the implementation of the introduction of Pak Kasur's children's songs can be seen from the children's ability to serve their own needs.